Strengthening Indonesia’s Strategic Trade Management Regulation Against Proliferation of Weapons of Mass Destruction - Purnama, Hadi Rahmat; Permana, Rizky Banyualam; Afriansyah, Arie (Faculty of Law, Universitas Brawijaya, 2024)
International law governing the control of WMD proliferation cannot solely focus on state actors but must also include non-state actors. To address the risks and combat the proliferation of WMD by non-state actors through the ordinary course of trade, the UNSC issued Resolution 1540, which contains the obligation to adopt domestic policies to prevent WMD proliferation. Indonesia has a legal obligation to comply with and implement this resolution under international law. This paper discusses the need assessment for Indonesia to enact a solid regulatory framework to implement Strategic Trade Management (STM). This paper questions how STM regulations are governed in the Indonesian context presently and how they should be regulated better to accommodate contemporary dynamics. This study is a legal and policy study involving literature review or desk research. Literature review involves gathering data and information such as literary texts, policy papers, legislative regulations, and other relevant documents. This study finds that even though Indonesia had already implemented some form of STM policy through export-import control and restriction (larangan dan pembatasan), it still left out the gap in properly regulating dual-use goods. Strategic goods regulation in Indonesian legislation is not intended in the context of dual-use goods, as export/import restrictions are designed to enhance Indonesia’s product competitiveness and market expansion, both domestically and internationally, increase the capabilities of exporters/importers, and enhance national product development and innovation. Implementation of STM policy One of the objectives that can be achieved is maintaining national security, especially in providing a sense of security for the Indonesian people and businesses. Implementing STM will also benefit businesses by reducing the risk of financial losses, such as being involved in export/import transactions prohibited by other countries or even by Indonesia. Moreover, by implementing STM, it is not unlikely that investment from countries with high technology will increase.